Digital Marketing Strategies: An Analysis of the Influence of Social Media on Consumer Purchase Decisions - Lestari, Feby Yulia; gunarto, Muji; Helmi, Sulaiman (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to analyze the influence of digital marketing strategies through social media on consumer purchase decisions. The research method used is a quantitative approach with survey techniques. Data was collected through an online questionnaire from 200 respondents who actively used social media. The results of the study show that content elements, interaction and consumer trust have a significant influence on purchase decisions. This finding provides important implications for the Company to maximize the use of social media as the main marketing platform.